Use of Metacognitive Strategies in Studies on Maqam-based Piano Pieces - Tuncer Tüfekçi, Ece; Albuz, Aytekin (Kastamonu Egitim Dergisi, 2025)
Purpose: The aim of this study is to examine the effect of using metacognitive strategies in piano education on metacognitive awareness and piano performance. In addition, it was aimed to reveal the metacognitive knowledge and metacognitive regulation skills used by the students in the process of studying maqam-based pieces. Design/Methodology/Approach: The research was conducted within the scope of mixed method. The quantitative dimension of the study used a one-group pretest-posttest experimental design. In the experimental process, individual piano lessons were held with the study group students (N=8) for 9 weeks, and the process of studying maqam-based pieces was carried out using metacognitive strategies. Quantitative data were obtained through the Metacognitive Awareness Inventory (MAI) and Piano Performance Rubric for Maqam-based Pieces (PPRMP). Within the qualitative dimension, the piece study diaries kept by the study group during the experimental process were analyzed. Findings: It was determined that the use of metacognitive strategies in the process of studying maqam-based pieces made a significant difference in the metacognitive awareness levels and piano performance levels of the study group. In the piece study diaries, many expressions were found in which students reflected their metacognitive knowledge and skills about their learning processes and piano performances. It was determined that students mostly used metacognitive monitoring and evaluation skills in the experimental process. Highlights: Although the metacognitive awareness of the study group regarding the knowledge of cognition dimension was higher than the regulation of cognition, it was determined that the activities related to the regulation of cognition were reflected more in the piece study diaries. Since piano education is an applied field, students' use of metacognitive editing skills and their frequent reflection of editing activities in their diaries are compatible with the structure of the process.